Psychometrics and validation of the EQ-5D-5L instrument in individuals with ischemic stroke in Lithuania - Taroza, Saulius; Burkauskas, Julius; Mickuviene, Narseta; Kazukauskiene, Nijole; Podlipskyte, Aurelija (Frontiers in Psychology, 2023)
Background: Experiencing a stroke is associated with a deterioration in health-related quality of life (HRQL). One of the generic tools used for HRQL assessment is the EuroQol instrument of five dimensions and five levels (EQ-5D-5L), which has not yet been validated in Lithuania. This study aimed to evaluate the EQ-5D-5L instrument validity, reliability and factor structure in a sample of Lithuanian individuals at the end of the first week after experiencing ischemic stroke (IS). Methods:The study had a cross-sectional design, including 134 individuals [61.9% men and 38.1% women; median (IQR) age was 66 years (59-73) years, in the final analysis. Alongside the EQ-5D-5L, psychological distress was evaluated using the Hospital Anxiety and Depression Scale (HADS), Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder Assessment-7 (GAD-7); neurological impairment with the National Institutes of Health Stroke Scale (NIHSS); and functional independence with the Barthel index (BI). Confirmatory factor analysis (CFA) was performed for validation of the factor structure. Results: The internal consistency of the EQ-5D-5L was 0.81. A significant ceiling effect (17.2%) of the descriptive part of the EQ-5D-5L was detected. Convergent validity of EQ-5D-5L descriptive system was confirmed, with significant correlations with the other scales used, except for the visual analogue scale. The two latent factor ("physical" and "emotional") model was confirmed by CFA, with acceptable fit [root mean square error of approximation (RMSEA) = 0.045, RMSEA 90% CI = 0.000-0.145; comparative fit indices (CFI) = 0.996; nonnormal fit index (NFI) = 0.983; Tucker-Lewis Index (TLI) = 0.936; χ2/df = 1.27)]. Conclusion: This study provides information on the psychometric properties of the EQ-5D-5L instrument in Lithuanian individuals, showing that the EQ-5D-5L descriptive system is a reliable and valid tool for HRQL assessment. The Lithuanian version of the descriptive part of the EQ-5D-5L is best expressed as a two-factor model, estimating the physical and emotional dimensions of HRQL in individuals who have experienced IS.